UMKM Tangsis 163 Sarang Gagak - Lidya Mudika Putri; Havivah; Humaniora (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Tangsis 163 Sarang Gagak is a small business in Padang that produces and sells snacks with local flavors. Located near the campus, Tangsis 163 utilizes digital platforms such as GoFood and Instagram to reach customers, especially students. With operating hours from afternoon to night, this MSME not only develops a culinary business but also supports the economic empowerment of the surrounding community through the creation of jobs and business opportunities.